Genetic Investigation of 261 Cases of Turner Syndrome Patients Referred to the Genetic Clinic - Dariush Farhud; Rojiar Asgarian; Amelia Seifalian; Paria Mostafaeinejad; Maryam Eslami (Tehran University of Medical Sciences, 2021)
Background: Turner syndrome (TS), also known as 45,X, is a genetic disorder caused by the partial or complete lack of an X chromosome. TS can cause a variety of medical and developmental conditions. We aimed to investigate TS mosaicism and variants pattern and research the presence of a correlation between the different variant's factors and TS occurrence. Methods: From 1984-2018, 100,234 patients referred to the Farhud Genetic Clinic, Tehran, Iran, for karyotyping were studied. TS was determined by the chromosomal assay, and the patients' karyotype was obtained from amniotic fluid and blood samples. Different variants of the TS diagnosed patients were investigated, including maternal and paternal age at pregnancy, parental consanguinity, and the presence/absence of a family history of the disease. Results: Overall, 261/100,234 (0.26%) were diagnosed with TS. These, 150 cases were identified to have the classical 45,X karyotype and 111 cases were identified to have either TS mosaicism or other less common variations of TS karyotyping. Higher parental age at pregnancy and TS data suggested that the occurrence of TS is significantly higher. Conclusion: Data suggest parental age at pregnancy is an important factor for TS occurrence. Hence, prenatal screening in these groups of parents recommended. This study also implicates early medical diagnostic testing before the onset of puberty or as soon as symptoms arise is essential for early treatment.